Using Pox-Neuro (Poxn) Mutants in Drosophila Gustation Research: A Double-Edged Sword - Chen, Yu-Chieh David; Park, Scarlet Jinhong; Ja, William W.; Dahanukar, Anupama (Frontiers in Cellular Neuroscience, 2018)
In Drosophila, Pox-neuro (Poxn) is a member of the Paired box (Pax) gene family that encodes transcription factors with characteristic paired DNA-binding domains. During embryonic development, Poxn is expressed in sensory organ precursor (SOP) cells of poly-innervated external sensory (p-es) organs and is important for specifying p-es organ identity (chemosensory) as opposed to mono-innervated external sensory (m-es) organs (mechanosensory). In Poxn mutants, there is a transformation of chemosensory into mechanosensory bristles. As a result, these mutants have often been considered to be entirely taste-blind, and researchers have used them in this capacity to investigate physiological and behavioral functions that act in a taste-independent manner. However, recent studies show that only external taste bristles are transformed in Poxn mutants whereas all internal pharyngeal taste neurons remain intact, raising concerns about interpretations of experimental results using Poxn mutants as taste-blind flies. In this review, we summarize the value of Poxn mutants in advancing our knowledge of taste-enriched genes and feeding behaviors, and encourage revisiting some of the conclusions about taste-independent nutrient-sensing mechanisms derived from these mutants. Lastly, we highlight that Poxn mutant flies remain a valuable tool for probing the function of the relatively understudied pharyngeal taste neurons in sensing meal properties and regulating feeding behaviors.